2022
DOI: 10.1002/ejp.1926
|View full text |Cite
|
Sign up to set email alerts
|

Living with endometriosis: Comorbid pain disorders, characteristics of pain and relevance for daily life

Abstract: Background Pain plays a central role in endometriosis. The complex relationship among pain characteristics, comorbid pain disorders and daily life represents a challenge for medical support. This multicentre cross‐sectional case–control study analysed the association between endometriosis‐related chronic pain and functions of daily life in 510 women with endometriosis, 265 (52%) who experienced chronic pain, either from endometriosis alone (N = 134, 26.3%) or in association with additional pain disorders (N = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 67 publications
0
18
0
Order By: Relevance
“…AM, defined as the presence of endometrial stroma and glands in the myometrium, is a prevalent disease in women that manifests varying symptomatology and adverse health outcomes. Among these, pain plays a central role in patients with AM ( Leuenberger et al, 2022 ). The management of AM is challenging and limiting.…”
Section: Discussionmentioning
confidence: 99%
“…AM, defined as the presence of endometrial stroma and glands in the myometrium, is a prevalent disease in women that manifests varying symptomatology and adverse health outcomes. Among these, pain plays a central role in patients with AM ( Leuenberger et al, 2022 ). The management of AM is challenging and limiting.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, by using the PDI, we compared the influence of pain on seven different facets of life [ 27 , 46 ]. A recent study published by Leuenberger and colleagues found that women with endometriosis were often severely impaired in multiple areas of daily life, with up to one third of them recognizing severe impairment in up to nine distinct areas of daily life [ 79 ]. Impaired role performance and social functioning has been described previously as well [ 80 , 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…Impaired participation in social activities, such as gatherings with friends or acquaintances, and occupational activities influenced global pain-induced disability to a lower extent, signaling than these activities are not as important as the ability for women with endometriosis to participate in family and recreational activities. Nevertheless, impaired socialization is a well-recognized factor with a negative influence on the quality of life of these patients [ 79 , 80 , 81 ]. Due to chronic pain, women with endometriosis report impaired occupational functioning, as they often cannot reach full professional fulfillment [ 79 , 80 , 81 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is categorized by three phenotypes: superficial peritoneal lesions, ovarian endometriomas and deep infiltrating endometriosis (Chapron et al, 2019). Disease prevalence (5%-10%) varies as much as its clinical symptoms, ranging from pelvic pain over infertility and fatigue to asymptomatic cases (Ramin-Wright et al, 2018;Taylor et al, 2021;Leuenberger et al, 2022). Among women with infertility the prevalence of endometriosis is estimated to account for 35%-50% (Giudice and Kao, 2004;Prescott et al, 2016;Sanchez et al, 2020).…”
Section: Introductionmentioning
confidence: 99%